Burundi : Poverty Reduction Strategy Paper; Preparation Status Report. (IMF Staff Country Reports; Country Report ;, 2005)
The Poverty Reduction Strategy Papers (PRSPs) on Burundi focus on the implementation of the interim PRSP. The implementation of the Interim PRSP has been undertaken in a relatively difficult social and political context, as Burundi is still involved in a process of normalizing and democratizing its political life. The experience acquired in the process of formulating the I-PRSP showed gaps in the dissemination of information to the public at large, as well as gaps in the understanding of the PRSP process on the part of all the social and economic development players in Burundi.